AACVD Synthesis and Characterization of Iron and Copper Oxides Modified ZnO Structured Films - Claros Vargas, Martha Carmiňa; Šetka, Milena; Yecid P., Jimenez; Vallejos Vargas, Stella (MDPI, 2020)
Non-modified (ZnO) and modified (Fe2O3@ZnO and CuO@ZnO) structured films are deposited via aerosol assisted chemical vapor deposition. The sulics of these structured films. Static water contact angle measurements for these structured films indicate hydrophobic behavior with the modified structures showing higher contact angles compared to the non-modified films. Overall, results show that the modification of ZnO with iron or copper oxides enhances the hydrophobic behavior of the surface, increasing the contact angle of the water drops at the non-modified ZnO structures from 122 degrees to 135 degrees and 145 degrees for Fe2O3@ZnO and CuO@ZnO, respectively. This is attributed to the different surface properties of the films including the morphology and chemical composition.

Non-modified (ZnO) and modified (Fe2O3@ZnO and CuO@ZnO) structured films are deposited via aerosol assisted chemical vapor deposition. The sulics of these structured films. Static water contact angle measurements for these structured films indicate hydrophobic behavior with the modified structures showing higher contact angles compared to the non-modified films. Overall, results show that the modification of ZnO with iron or copper oxides enhances the hydrophobic behavior of the surface, increasing the contact angle of the water drops at the non-modified ZnO structures from 122 degrees to 135 degrees and 145 degrees for Fe2O3@ZnO and CuO@ZnO, respectively. This is attributed to the different surface properties of the films including the morphology and chemical composition.
AACVD Synthesis and Characterization of Iron and Copper Oxides Modified ZnO Structured Films
Keywords: AACVD; zinc oxide; iron oxide; copper oxide; structured films; water contact angle; AACVD; zinc oxide; iron oxide; copper oxide; structured films; water contact angle